Do We Need Autistic Autism Researchers to Understand Autism? - Kędra, Agnieszka (ETHICS IN PROGRESS, 2023)
The assumption that autistic individuals do not have the theory of mind – the social-cognitive ability to understand other people by attributing mental states to them – has been widespread in the psychological literature. However, the empirical evidence from the original research and its replications failed to prove and support autistic mind-blindness. Yet, it is still present in literature on autism spectrum. Meanwhile, convincing research, that has been conducted among autistic researchers and their allies, is often overlooked by non-autistic specialists. This paper focuses on how autistic autism researchers have been influencing their field of study and how academy can benefit from their work.